Overexpression of miR‐455‐5p affects retinol (vitamin A) absorption by downregulating STRA6 in a nitrofen‐induced CDH with lung hypoplasia rat model. Issue 6 (1st April 2020) - Zheng, Jintao; He, Qiuming; Tang, Huajian; Li, Jiequan; Xu, Huiyu; Mao, Xiangming; Liu, Guoqing
Abstract: Lung hypoplasia is the main cause of congenital diaphragmatic hernia (CDH)‐associated death but pathogenesis remains unclear. MiR‐455‐5p is involved in lung hypoplasia. We hypothesized that nitrofen causes abnormal miR‐455‐5p expression during lung development and designed this study to determine the relationship between miR‐455‐5p, stimulated by retinoic acid 6 ( STRA6 ), and retinol in a nitrofen‐induced CDH with lung hypoplasia rat model. Nitrofen or olive oil was administered to Sprague‐Dawley rats by gavage on day 9.5 of gestation, and the rats were divided into a nitrofen group and a control group (n = 6). The left lung of fetuses was dissected on day 15.5. The expression of miR‐455‐5p or STRA6 messenger RNA (mRNA) was determined by quantitative real‐time polymerase chain reaction. Average integrated optical density (IOD) of STRA6 protein was determined by immunofluorescence histochemistry. The average retinol level was detected by enzyme‐linked immunosorbent assay (n = 6 lungs, respectively). Compared with the control group, the nitrofen group exhibited significantly increased miR‐455‐5p expression levels (29.450 ± 9.253 vs 5.955 ± 2.330; P  = .00045) and significantly decreased STRA6 mRNA levels (0.197 ± 0.097 vs 0.588 ± 0.184; P  = .0047). In addition, the average IOD of the STRA6 protein was significantly lower in the nitrofen group (805.643 ± 291.182 vs 1616.391 ± 572.308, P  = .015), and the average retinol level was significantly reduced (4.013 ± 0.195 vs 5.317 ± 0.337 µg/L, P  = .000). In summary, the overexpression of miR‐455‐5p affected retinol absorption by downregulating STRA6 in the nitrofen‐induced CDH with lung hypoplasia rat model, and this downregulation may be one cause of CDH with lung hypoplasia.